PENERAPAN PROBLEM BASED-LEARNING MELALUI LESSON STUDY PADA PEMBELAJARAN PPKN UNTUK MENINGKATKAN PARTISIPASI AKTIF DAN KERJASAMA SISWA DALAM DISKUSI KELOMPOK - Ken Restisiwi; Lutfi Istikharoh (Khazanah Pendidikan, 2020)
ABSTRACTThis article presents the result of implementing Problem-based Learning throughLesson Study in Civics class as an effort of enhancing students’ participation andcollaboration during class discussions. The implementation of Problem-based Learningthrough Lesson Study was conducted in a private school under Muhammadiyahorganization in Distric Purbalingga, Central Java, namely MTs Muhammadiyah 01Purbalingga. In Civics Class at the school investigated, the learning process wascommonly dominated by lecturing session which made the students passive and foundmonotonous atmosphere of learning which consequently resulted on meaninglesslearning. This condition affected to the students’ activeness which belonged to lowcategory. Therefore a better design of learning by implementing Problem-basedLearning through Lesson Study was needed to cope with the problem. Lesson Study wasdone in 2 cycles and is still continuing until now. The action was intended to make thestudents more active and participative during the Civics lesson especially in classdiscussion sessions. The method which was used is qualitative method with 36 studentsin grade 8E of MTs Muhammadiyah 01 Purbalingga participated. During two times ofplan-do-see actions in Lesson Study, 8 of 9 groups in Civics class or 80% of the wholestudents was good at participating in group and class discussions. The finding found inthe two cycles of Lesson Study gives a proof that the implementation of Problem-basedLearning contributes positively to the students’ participation and collaboration in Civicsclass.Keywords: Plan, Do, See, Participation, Collaboration